Dylematy oceniania wczesnoszkolnego - Piątek, Teresa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Ocenianie wczesnoszkolne winno służyć dziecku, jego rozwojowi i w konsekwencji prowadzić do zdobycia umiejętności adekwatnej samooceny, tak ważnej z punktu widzenia wykorzystywania swojego potencjału, swoich mocnych stron w życiu. Tymczasem analiza szkolnej rzeczywistości ukazuje bardzo tradycyjne podejście nauczycieli do oceniania uczniów w klasach I–III szkoły podstawowej. Pomimo konieczności stosowania oceny opisowej na koniec semestru i na koniec roku nauczyciele edukacji wczesnoszkolnej rezygnują z niej w trakcie bieżącego oceniania postępów swoich uczniów, stosując ocenę szacunkową wyrażoną stopniem szkolnym.

Early education evaluation should serve the child, its development and, consequently, lead to the ability of adequate self-evaluation, so important in terms of using its own potential and personal strengths in life. Meanwhile, the analysis of the school reality demonstrates a very traditional approach taken by teachers to evaluate students in grades I to III in the primary school. Despite the need for providing a descriptive assessment at the end of the semester and at the end of the year, primary school teachers are abanding such approach (during on-going grading of their student’s progresses) and istead use the so called estimation grade in the form of a typical school grade.
Dilemas of Early Education Evaluation
Keywords: ocena szkolna; ocena opisowa; ocenianie; kontrola; samokontrola; samoocena; school grade; descriptive grade; assessment; control; self-control; self-evaluation